Integration Of Project Based Learning (PjBL) And Game Based Learning (GBL) In A Deep Learning Approach - Moch Bayu Ibrahim S; Anisa Khayati Nur Kafah; Rika Yuliana; Af Idatul Amalia (Insights: Journal of Primary Education Research, 2025)
Amidst the demands of 21st-century learning, which emphasizes active engagement, deep understanding, and strengthening student motivation, innovation in learning models has become an inevitable necessity in elementary schools. This study aims to analyze the effectiveness of integrating Project-Based Learning (PjBL) and Game-Based Learning (GBL) in improving students’ learning outcomes, motivation, and engagement in science learning at SD Negeri Mekarwangi and SD Negeri Jatijaya. Employing a mixed-methods approach, the research combines a quantitative experiment using a pretest–posttest control group design with qualitative data obtained through interviews and classroom observations. The results of the independent sample t-test indicate a significant difference between the experimental and control groups (p < 0.05), with the experimental group achieving nearly twice the gain score, demonstrating stronger conceptual understanding. Motivation scores in the experimental group were categorized as “very high,” influenced by elements of challenge, instant feedback, and engaging game dynamics. Qualitative findings further reveal improvements in students’ confidence, collaboration, and deeper conceptual comprehension. Overall, the integration of PjBL and GBL is proven effective in creating more active, meaningful learning experiences and fostering deep learning.